2019
DOI: 10.1165/rcmb.2018-0176oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia-induced Cellular Senescence in Fetal Airway Smooth Muscle Cells

Abstract: Supplemental O 2 (hyperoxia; 30-90% O 2 ) is a necessary intervention for premature infants, but it contributes to development of neonatal and pediatric asthma, necessitating better understanding of contributory mechanisms in hyperoxia-induced changes to airway structure and function. In adults, environmental stressors promote formation of senescent cells that secrete factors (senescence-associated secretory phenotype), which can be inflammatory and have paracrine effects that enhance chronic lung diseases. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…In addition to replicative senescence induced by aging, several other factors contribute to the development of stress-induced senescence in the lung, including radiation therapy, smoking, mechanical ventilation, and chronic use of supplemental oxygen (Figure 1). [24,[67][68][69][70], which supports the concept that other processes besides natural aging lead to senescence. Similarly, aged mice, which likely exhibit increased lung senescence, also exhibit enhanced lung permeability and increased levels of reactive oxygen species in response to an LPS challenge, which is linked to deficient Nox4 (a ROS-generating mitochondrial protein) ubiquination [86].…”
Section: Cellular Senescence In the Lungsupporting
confidence: 57%
“…In addition to replicative senescence induced by aging, several other factors contribute to the development of stress-induced senescence in the lung, including radiation therapy, smoking, mechanical ventilation, and chronic use of supplemental oxygen (Figure 1). [24,[67][68][69][70], which supports the concept that other processes besides natural aging lead to senescence. Similarly, aged mice, which likely exhibit increased lung senescence, also exhibit enhanced lung permeability and increased levels of reactive oxygen species in response to an LPS challenge, which is linked to deficient Nox4 (a ROS-generating mitochondrial protein) ubiquination [86].…”
Section: Cellular Senescence In the Lungsupporting
confidence: 57%
“…Diabetes/ Obesity [109,110,112,[116][117][118] Cardiac dysfunction [13,18,114] Vascular hyporeactivity/ calcification [114] AV fistulae [115] Frailty [21,51,52,87] Age-related muscle loss (Sarcopenia) [119] Chemotherapy complications [21,51,93,120,121] Radiation complications [122] Cancers [51] Bone marrow transplant complications [120] Organ transplantation complications [123,124] Myeloma/ MGUS [125] Age-related cognitive dysfunction [126] Alzheimer's disease [23,127] Parkinson's disease [76] Amyotrophic lateral sclerosis [128] Ataxia [87] Obesity-related neuropsychiatric dysfunction [24] Renal dysfunction [111,129] Urinary incontinence [87] Osteoporosis [14,71,130] Osteoarthritis [131] Age-related intervertebral disc disease [87,132] Idiopathic pulmonary fibrosis [21,133]…”
Section: Condition Referencesmentioning
confidence: 99%
“…Some asthmarelated factors have shown to induce senescence in smooth muscle cells. In vitro study showed that hypoxia induced cellular senescence in fetal ASMCs, leading to the upregulation of proinflammatory and profibrotic mediators, as well as increased contractility, which conduces to inflammation, tissue remodeling and airway obstruction (Parikh et al, 2019a). IgE and its receptor play an important role in the pathogenesis of allergic diseases like asthma.…”
Section: Mesenchymal Cell Senescencementioning
confidence: 99%
“…This indicates that there is premature senescence triggered at young age in asthma. In this regard, studies have demonstrated that hypoxia in infants, air pollutants exposure, and allergen challenge in childhood/adolescence could induce underlying senescence process (Deng et al, 2013;Chan et al, 2016Chan et al, , 2017Lee et al, 2017Lee et al, , 2019Parikh et al, 2019a). Such stressors might induce cellular senescence in airway epithelial cells, mesenchymal cells or immune cells, leading to their dysfunction and facilitating the initiation of asthma.…”
Section: Specific Role Of Cellular Senescence In Asthma Different Fromentioning
confidence: 99%